Numeracy Junior High School Students in Completing AKM Equivalent Questions Reviewed from Adversity Quotient - Ambarsari, Aprilia; Masriyah, Masriyah (JUPE : Jurnal Pendidikan Mandala, 2025)
The purpose of this study is to describe the numeracy of junior high school students of climber, camper, and quitter types in solving AKM equivalent problems. This type of research is descriptive qualitative research. The instruments in this study consisted of the main instrument, namely the researcher, and supporting instruments, namely the ARP test, math ability test, AKM equivalent problems, and interview guidelines. This research was conducted at SMPN 32 Surabaya in class VIII-E, and then 3 main subjects representing adversity quotient types were selected. The results of this study found that climber-type students successfully fulfill all numeracy indicators. At the comprehension level, they can analyze information and then represent the data in mathematical form. At the application level, one can design strategies by applying mathematical concepts to solve problems. In addition, at the reasoning level, climber-type students are able to interpret results, draw logical conclusions, and provide strong reasons to support their answers. Meanwhile, camper-type students at the comprehension level can identify information and present it in mathematical form. At the application level, camper-type students can design strategies and apply mathematical concepts. However, at the reasoning level, camper students have not been able to interpret the results of the relationship of information in the problem. Quitter-type students cannot reach higher cognitive levels, especially at the application and reasoning stages. Thus, quitter-type students can only reach the comprehension level, which means understanding information and representing data.